Numerical Investigation of Ti6Al4V Gradient Lattice Structures with Tailored Mechanical Response. Issue 4 (11th February 2022) - Mora Sierra, Daniel Camilo; Heydari Astaraee, Asghar; Guagliano, Mario; Bagherifard, Sara
Abstract : Open porous lattice structures have found a wide range of applications as lightweight load‐bearing and energy absorbent structures in various fields. A common requirement for any application is the preliminary assessment of the mechanical response of the proposed architecture. Herein, uniform and continuous functionally graded lattice structures (FGLSs) made of titanium alloy, Ti–6Al–4V, are designed using cubic and pillar octahedron unit cells at overall porosities of 60%, 75%, and 85%. The lattice morphology is modulated using axial, dense‐in, and dense‐out gradient strategies. The mechanical performance of the structures is studied using numerical simulations implementing damage initiation and evolution under quasi‐static compression. The proposed models could properly simulate the mechanical properties and failure behavior of the lattice structures. The designed FGLSs displays a crushing behavior starting from the lower relative density layers toward the higher relative density ones. Cubic and pillar octahedron‐based structures exhibit stretch‐ and bending‐dominated deformation behaviors, respectively. The power‐law analysis verified by the Gibson–Ashby model is used to assess the mechanical response of the FGLSs. The effect of the gradient strategies on the mechanical properties as well as their adaptability for orthopedic implants is discussed in detail. Abstract : Lattice structures are of interest for their lightweight and notable mechanical performance. Their mechanical response can be modulated by changing the topology of their building block unit cell. This study, however, shows the high potential to tune the mechanical response of these structures by implementing various gradient strategies to adjust the geometrical aspects for any characteristic unit cell shape.